If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(6 + -1w) = -2w + -12 + 4w (6 * -4 + -1w * -4) = -2w + -12 + 4w (-24 + 4w) = -2w + -12 + 4w Reorder the terms: -24 + 4w = -12 + -2w + 4w Combine like terms: -2w + 4w = 2w -24 + 4w = -12 + 2w Solving -24 + 4w = -12 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -24 + 4w + -2w = -12 + 2w + -2w Combine like terms: 4w + -2w = 2w -24 + 2w = -12 + 2w + -2w Combine like terms: 2w + -2w = 0 -24 + 2w = -12 + 0 -24 + 2w = -12 Add '24' to each side of the equation. -24 + 24 + 2w = -12 + 24 Combine like terms: -24 + 24 = 0 0 + 2w = -12 + 24 2w = -12 + 24 Combine like terms: -12 + 24 = 12 2w = 12 Divide each side by '2'. w = 6 Simplifying w = 6
| 0.8b=10.4 | | 1+3(16-2x)=0 | | 1+3(16-2x)= | | x+15=-5 | | x^2-24x+108=0 | | 9=-5(4x+2)+21x | | 4x=5y-17 | | .75w+8=.3w-7 | | -2(2+5n)+16(5-9n)= | | -30=j | | 6a^2+6a=6+6a | | 14=j-44 | | x=3.14(36)8-3.14(16)8 | | 4x^2-48x+25=0 | | 64x^2+144x+81=0 | | a^2+6a=1-a | | x=3.14(12)1.5(1.5)+2(.5)3(4) | | -2(x+3)+3x=15 | | 3t^2=16 | | 7-2a=-5 | | 18x-9=12x-51 | | x-ax=10 | | 4p^2-13p=-15+3p | | 5r^2+5=130 | | 2x^4-20x^3+70x^2-100x+48=0 | | 8y-5y+y= | | (x^2+5x-1)+(-2x^2-2x+5)+(-3x^2+4)= | | 5r^2+5=30 | | (9x^4+7)(9x^4-7)= | | x=3.14(30)7.5(7.5)+5(15)30 | | x^5+4x^4-2x^3-8x^2= | | 2(6x-4)=4x-10 |